2020
DOI: 10.3390/ani10071186
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Water-Soluble Antioxidants in Fodder Additives and Sheep Blood Serum by Amperometric and Biochemical Methods

Abstract: The effects of chitosan as feed additive for animals (FAFAs) on various digestive processes are an important to study because of the animal nutrition and production quality, healthcare and farming. The aims of this study were to evaluate the total amount of water-soluble antioxidants (TAWSA) of chitosan and high protein microbiologically synthesized concentrate as FAFAs; to assess the effect of these FAFAs on TAWSA values, parameters of sheep blood serum and rumen content by biochemical, physical and chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Some of these biochemical parameters differed slightly in a number of values: urea—by −5.3% and +4.7%, and creatinine—by −14.0% and −7.8%, for groups 2 and 3 compared to group 1, respectively ( Table 1 , Table 2 and Table 3 ). This is normal for a young growing organism and indicates an improvement in protein metabolism in a number of animals [ 37 , 38 , 39 ]. Similar values of the total protein content in the blood serum of piglets were also noted by other authors [ 9 , 10 , 37 , 38 , 39 ], and it was indicated that this parameter “differed by variability” [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of these biochemical parameters differed slightly in a number of values: urea—by −5.3% and +4.7%, and creatinine—by −14.0% and −7.8%, for groups 2 and 3 compared to group 1, respectively ( Table 1 , Table 2 and Table 3 ). This is normal for a young growing organism and indicates an improvement in protein metabolism in a number of animals [ 37 , 38 , 39 ]. Similar values of the total protein content in the blood serum of piglets were also noted by other authors [ 9 , 10 , 37 , 38 , 39 ], and it was indicated that this parameter “differed by variability” [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is normal for a young growing organism and indicates an improvement in protein metabolism in a number of animals [ 37 , 38 , 39 ]. Similar values of the total protein content in the blood serum of piglets were also noted by other authors [ 9 , 10 , 37 , 38 , 39 ], and it was indicated that this parameter “differed by variability” [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Зокрема, важливе значення мають мінеральні елементи, ферменти та амі-нокислоти. Використання цих біологічно активних речовин дає змогу найбільш ефективно використовувати поживні речовини раціону, що забезпечує максимально можливу генетично обумовлену продуктивність тварин, високу відтворювальну здатність [14][15][16].…”
Section: білоцерківський національний аграрний університетunclassified